Gut-Antimicrobial Peptides: Synergistic Co-Evolution with Antibiotics to Combat Multi-Antibiotic Resistance - Piyush Baindara; Santi M. Mandal (MDPI AG, 2023)
Due to huge diversity and dynamic competition, the human gut microbiome produces a diverse array of antimicrobial peptides (AMPs) that play an important role in human health. The gut microbiome has an important role in maintaining gut homeostasis by the AMPs and by interacting with other human organs via established connections such as the gut-lung, and gut-brain axis. Additionally, gut AMPs play a synergistic role with other gut microbiota and antimicrobials to maintain gut homeostasis by fighting against multi-antibiotic resistance (MAR) bacteria. Further, conventional antibiotics intake creates a synergistic evolutionary pressure for gut AMPs, where antibiotics and gut AMPs fight synergistically against MAR. Overall, gut AMPs are evolving under a complex and highly synergistic co-evolutionary pressure created by the various interactions between gut microbiota, gut AMPs, and antibiotics; however, the complete mechanism is not well understood. The current review explores the synergistic action of gut AMPs and antibiotics along with possibilities to fight against MAR bacteria.